The chloroplast genome of the Peltigera elisabethae photobiont Chloroidium sp. W5 and its phylogenetic implications - Adil, Guldiyar; Liu, Shenglei; Bao, Xiaoyan; Mamut, Reyim (Frontiers in Genetics, 2025)
IntroductionLichens are globally distributed symbiotic organisms comprising fungi (mycobionts) and photosynthetic partners (photobionts), with exceptional adaptability to extreme environments. Despite growing interest in lichen symbiosis, chloroplast genome data for photobionts remain scarce, hindering insights into symbiotic coevolution and genomic architecture.MethodsTo address this gap, we characterized the chloroplast genome of Chloroidium sp. W5, a photobiont of the lichen Peltigera elisabethae, using next-generation sequencing. The circular genome (190,579 bp) was assembled and annotated using a combination of bioinformatics tools, including GetOrganelle for genome assembly and GeSeq for annotation. We conducted a comprehensive analysis of the genome’s structure, gene content, and repetitive elements. Codon usage patterns were assessed using MEGA 11, and phylogenetic relationships were inferred using maximum likelihood analysis with IQ-tree.ResultsThe circular genome (190,579 bp) lacks the canonical quadripartite structure (LSC/IR/SSC) and exhibits a strong AT bias (56.1%). Annotation identified 110 functional genes, including 79 protein-coding genes, 28 tRNAs, and 3 rRNAs. Repetitive sequence analysis revealed 5,000 dispersed repeats (2.62% of the genome), predominantly forward and palindromic types, with SSR loci showing a significant A/T preference. Codon usage analysis demonstrated a pronounced bias toward A/U-ending codons (RSCU > 1), suggesting translational adaptation to symbiotic nutrient constraints. Phylogenetic reconstruction robustly placed Chloroidium sp. W5 within the Watanabeales clade (ML = 100), while synteny analysis revealed extensive genomic rearrangements compared to close relatives.DiscussionThese findings enrich the chloroplast genome database for lichen photobionts, shedding light on symbiosis-driven genomic plasticity and providing a foundation for studying host-photobiont coevolution and lichen ecological adaptation.